Formulation of Criminal Law System Policy in the Settlement of Compensation for Corruption Crimes (Discourse Journal on Law and Society, 2025)
Corruption in Indonesia is not merely a moral transgression but an extraordinary economic crime that depletes national resources. The ultimate objective of corruption eradication, therefore, must be the restoration of state financial losses (asset recovery).  However, the current formulation of the criminal law system specifically Article 18 of Law No. 31 of 1999 contains a critical policy flaw. The provision of "Subsidiary Imprisonment" (Pidana Pengganti) allows convicts to substitute their financial restitution obligations with a disproportionately short prison term. This mechanism inadvertently provides an economic incentive for corruptors to conceal assets and choose imprisonment, resulting in significant state revenue loss. This study aims to critique the current penal policy formulation and propose a comprehensive reformulation of the compensation system. The research employs a normative-juridical method with a statutory and conceptual approach, utilizing the "Economic Analysis of Law" theory to evaluate the efficiency of sanctions. The study argues that the penal policy must shift from a "person-based" approach (in personam) to an "asset-based" approach (in rem). It is imperative to abolish the subsidiary imprisonment option for high-value corruption and implement "Non-Conviction Based Forfeiture" to maximize the recovery of state losses. Furthermore, this policy shift requires law enforcers with high-level cognitive skills to trace complex financial trails.